Cost-effectiveness of pharmacy-led versus conventionally delivered antiviral treatment for hepatitis C in patients receiving opioid substitution therapy: An economic evaluation alongside a pragmatic cluster randomised trial. Issue 6 (December 2022) - Myring, G.; Lim, A.G.; Hollingworth, W.; McLeod, H.; Beer, L.; Vickerman, P.; Hickman, M.; Radley, A.; Dillon, J.F.
Summary: Background: Elimination targets for hepatitis C have been set across the world. In the UK almost 90% of infections are in people who inject drugs. Evidence shows community case-finding is effective at identifying and treating undiagnosed patients. The aim of this analysis was to assess, from a healthcare provider perspective, the cost-effectiveness of a new pharmacist-led test and treat pathway for hepatitis C in opioid agonist treatment (OAT) patients attending community pharmacies compared to conventional care. Methods: In a cluster randomised controlled trial, pharmacies were randomised to the pharmacist-led or conventional care pathway. Mean cost per OAT patient and per patient initiating treatment was identified for each pathway. A Markov model tracking disease progression was developed, with a 50-year time horizon and 3·5% time discount rate, to estimate the incremental cost-effectiveness ratio (ICER) per quality-adjusted life-year (QALY) gained and the probability of being cost-effective at a £30, 000 per QALY willingness-to-pay threshold. Probabilistic sensitivity analysis was performed for a range of drug discounts, re-infection rates, and model assumptions. Findings: Mean cost per OAT patient (£3, 674 vs £1, 965) and per patient initiating treatment (£863 vs £404) was higher in the pharmacist-led pathway, due to higher uptake of testing and pharmacist time requirements. Over a 50-year time horizon the ICER per QALY gained was £31, 612 at NHS indicative price for treatment (£38, 979 for 12 weeks) and 12·1/100 person-years re-infection rate, reducing to £21, 027/£10, 220/-£501 per QALY gained with 30%/60%/90% drug price discounts and £25, 373/£21, 738/£14, 912 per QALY gained at re-infection rates of 8/5/2 per 100 person-years. At 30%/60%/90% drug discount rates, the pharmacist-led pathway has an 80%/98%/100% probability of being cost-effective. Interpretation: The pharmacist-led pathway is effective at increasing testing and treatment uptake, with cost-effectiveness being highly dependent on drug price discounts. Funding: Trial funding provided by the Scottish Government, Gilead Sciences, and Bristol-Myers Squibb.